Weighted Boost Spearman Correlative Dual Cluster Head for Robust Transmission in Wsn - Bhatt, Neha (Mathematical Statistician and Engineering Applications, 2021)
Wireless Sensor Networks (WSNs) are widely used in various applications, but they are often subject to environmental factors that result in poor network performance and packet loss. To address this challenge, correlation-based routing algorithms have been proposed. However, the performance of these algorithms degrades when the correlation between nodes is low. In this paper, we propose a Weighted Boost Spearman Correlative Dual Cluster Head (WBSCDCH) approach for robust transmission in WSNs. The proposed approach uses weighted boosting to assign higher transmission power to cluster heads with low correlation and utilizes dual cluster heads for efficient data collection and transmission. Our simulation results show that the proposed approach outperforms existing algorithms in terms of packet delivery ratio, energy consumption, and end-to-end delay. This paper contributes to the field of WSNs by providing a novel approach for improving the robustness of data transmission in WSNs.